Accommodation of "Merdeka Belajar" Spirit in Islamic Boarding School Nurul Huda Pakandangan Sumenep - Muh. Rusli; AH Mansur; Ali Ridho; Ahmad Hanif Fahruddin (TADRIS: Jurnal Pendidikan Islam, 2022)
Merdeka Belajar gives freedom to develop the students’ talent without the obstacles of formal rules that shackle the creativity of students. The study of independent learning in the context of an empirical boarding school is very rarely done. Even though pesantren are considered to be independent in learning. This study aims to describe clearly how Islamic boarding schools accommodate the free spirit of learning in their education system. This study uses a qualitative approach with in-depth interview data networks, observations and documentation. The results of this study indicate that there is accommodation of an independent spirit of learning at the Nurul huda Pakandangan Islamic boarding school with three main things, firstly accommodation of an educational vision that leads to an independent spirit of learning by integrating religious and scientific knowledge. Facilitating the development of the potential of students as a whole with skills. empowerment of knowledge, skills, experience, attitudes and assessments based on national and global standards. Secondly, Students can freely determine their competence while remaining teacher-minded. Third is the accommodation of educational innovation in the service program in accordance with the educational goals of the pesantren which requires them to return to the community. Fourth Islamic boarding schools are gender responsive by accommodating equality education.